Cultivation of Lemon Grass (Cymbopogon flexuosus, ’CKP-25’) under Poplar Based Agroforestry System - Yadava, Anil Kumar (Indian Forester, 2001)
Lemon grass was tested with three spacing and four fertility levels under Poplar (Populus deltoides ’G-3’) for its performance in Kumaun foothills for two years (1993-1994). The treatment combination S2F3 (spacing 45 x 45 cm and fertility level N250P100K80) proved to be superior in respect of number of tillers (78 and 114), plant height (153 and 150 cm), herbage yeild (57.6 and 68 t/ha) and oil yield (260.9 and 309.4 kg/ha) when compared to other treatments in the first and second year, respectively. The soil content and quality of oil was similar in all the treatments.